TINJAUAN YURIDIS KEDUDUKAN OTORITAS JASA KEUANGAN DALAM PENGAJUAN PERMOHONAN PERNYATAAN PAILIT TERHADAP PERUSAHAAN ASURANSI - Neneng Karlina; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Article 50 Paragraph (1) of Law Number 40 Year 2014 About the insurance stating that, Request statement of bankruptcy against the insurance company and the company may only be submitted by the Financial Services Authority. The lack of power in the application for a declaration of bankruptcy centralized in one institution, namely the financial Services Authority become more complex issues related to the rule of law in bankruptcy, the insurer considered immune to bankruptcy. The purpose of this thesis, namely: First, to find out why the Financial Services Authority has authorized the application for a declaration of bankruptcy of the insurance company for the benefit nasbah, Secondly, to find out how the position of the Financial Services Authority in the application for a declaration of bankruptcy of the insurance company. This type of research can be classified in this type of normative juridical research, which is a type of research that discusses the principles of law. The study authors do by examining the library materials or secondary data such as legislation and books written by lawyers associated with the title of the research, articles, journals, and other sources. From the research problem it is clear that the consideration given authority filing a bankruptcy petition to the Financial Services Authority is because easy terms in bankruptcy is the debtor has two creditors that the debt has matured and could be charged, the authority in the application for a declaration of bankruptcy for an insurance company that is centralized on one institute aims to ensure the interests of all parties in order to create a stable economic system the country through the financial services sector. The position of the Financial Services Authority in the application for a declaration of bankruptcy of the insurance company is the authority granted by the state to protect the interests of the community as users of financial services that were previously owned by the Ministry of Finance and turning to the Financial Services Authority as a result of the enactment of Law No. 21 of 2011 About the authority financial services, based on the principle of lex posteriori derogat legi priori where the provisions of the new legislation would override the laws of time, then all the authority of the Minister of Finance including those relating to the insurance switch from the Minister of Finance to the financial Services authority, including for the -things pertaining to bankruptcy issues. Related problems bankruptcy insurer, authorized the Financial Services Authority. Keywords : Authority - Authority - Bankrupt Financial Services – Insurance Company